2007
DOI: 10.1142/s0218271807010213
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity of Electrodynamics as a Source of Matter Creation in a Flat FRW Cosmology

Abstract: The thermodynamics of cosmological matter creation has been extensively investigated in the literature. In the context of general relativity, the particle production in the cosmological models is due to mechanisms such as an imperfect fluid with bulk viscosity or the decaying vacuum. Another interesting proposal is matter creation in cosmologies with variation of fundamental constants. In this work, we study the nonlinearity of the electrodynamics as a source of matter creation in cosmological models with flat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Over the last few years there has been a significant amount of interest in cosmological models involving nonlinear electromagnetic fields [1,2,3]. If the early universe is dominated by radiation governed by Maxwell's equations it is well known that there will be a spacelike initial singularity in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years there has been a significant amount of interest in cosmological models involving nonlinear electromagnetic fields [1,2,3]. If the early universe is dominated by radiation governed by Maxwell's equations it is well known that there will be a spacelike initial singularity in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Ergospheres are given by V = 0 and the velocity of light surface is given by X = 0. Comparing our rotating spacetime (13) with the former metric, one can show that X = 0 leads to…”
Section: Properties Of the Solutionsmentioning
confidence: 97%
“…(1), (3) and (5) show that for s = 1 (linear case) and 1/2 < s ≤ n/2, the metric of Eqs. (13) and (15) has two inner and outer event horizons located at r − and r + , provided the mass parameter m is greater than m ext given as These solutions present naked singularity for m < m ext and when m = m ext , we have an extreme black brane with horizon radius…”
Section: Properties Of the Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These theories are richer than linear electrodynamics and can reduce to linear Maxwell theory. In addition, several authors have studied cosmological models, including nonlinear electrodynamic fields [13][14][15][16][17][18]. Some authors have found charged black hole and black brane solutions coupled to nonlinear electrodynamics [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%